What is the role of beta-blockers in a contemporary treatment cohort of patients with acute coronary syndrome? - Timóteo, Ana Teresa (2018)
Copyright © 2018 Sociedade Portuguesa de Cardiologia. Publicado por Elsevier España, S.L.U. All rights reserved.